Residual compressive strength of lightweight foamed concrete after exposure to high temperatures - Othuman Mydin, Md Azree; Mohd Yunos, Mohd Yazid; Mohd Nawi, Mohd Nasrun; Che-Ani, Adi Irfan (Trans Tech Publications, Switzerland, 2015)
Even though lightweight foamed concrete has low mechanical properties compared to normal weight concrete, there is a potential of using this material as partition or load-bearing wall in low-rise residential construction.Before it can be considered for use as a load-bearing element in the building industry, it is necessary to acquire reliable information of its mechanical properties at ambient and high temperatures for quantification of its fire resistance performance. This paper will present the results of experiments that have been carried out to examine and characterize the residual Compressive strength of foamed concrete after high temperatures. Foamed concrete with 700 kg/m 3 and 1000 kg/m 3 density were cast and tested. The compression tests were carried out at ambient temperature, 100, 200, 300, 400, 500 and 600°C.